2023
DOI: 10.3389/fpubh.2023.1213403
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study between traditional and sports school uniforms on cardiorespiratory and muscular fitness and waist-height-to-ratio in adolescents

Abstract: BackgroundImproving health of children and adolescents is crucial for their overall development. Therefore, it is essential to explore factors that may influence their health at both the public health and school system levels.ObjectiveThis study compares physical fitness components and waist-height-to-ratio (WHtR) in adolescents according to school uniforms, namely the traditional uniform (i.e., shirt and school necktie in boys and skirt and blouse in girls) and the sports uniform (i.e., polo shirts or t-shirt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
0
0
Order By: Relevance
“…School uniforms are common in many primary and secondary school settings globally. 24 While some researchers have explored their relationship with other outcomes 25 , 26 , 27 , 28 , 29 , 30 (e.g., academic achievement 27 , 31 and social behavior 28 ), finding no or inconsistent correlations, studies examining associations with gender inequalities in physical activity are limited. Previous researchers who explored UK adolescent girls’ experiences of physical activity at school through the lens of comfort theory 32 found that female participants perceived their PE uniform as a barrier to physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…School uniforms are common in many primary and secondary school settings globally. 24 While some researchers have explored their relationship with other outcomes 25 , 26 , 27 , 28 , 29 , 30 (e.g., academic achievement 27 , 31 and social behavior 28 ), finding no or inconsistent correlations, studies examining associations with gender inequalities in physical activity are limited. Previous researchers who explored UK adolescent girls’ experiences of physical activity at school through the lens of comfort theory 32 found that female participants perceived their PE uniform as a barrier to physical activity.…”
Section: Introductionmentioning
confidence: 99%